2010
DOI: 10.1007/s10600-010-9604-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinone, naphthalene, and naphthoquinone components of Asphodeline lutea

Abstract: The genus Asphodeline belongs to the family Asphodelaceae, subfamily Asphodeloideae. The 1,8-dihydroxyanthraquinones based on a chrysophanol unit are characteristic compounds of this subfamily. Anthraquinones, flavonoids, oxepines, and sesquiterpene lactones have been reported to occur in the genus Asphodeline [1][2][3][4].Asphodeline lutea is a perennial plant growing in the Mediterranian region. The only report found on this plant species reveals the presence of 1,8-dihydroxyanthraquinones, flavonoids, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Likewise, A.globifera is used as a medicament for alleviating haemorrhoids symptoms, A. lutea and A. taurica are consumed in salads (Tuzlaci, 1985). Owing to their potential use in different purposes, several studies focused on secondary metabolites especially antraquinones, sesquiterpene and naphthalene components of Asphodeline species (Ulubelen et al, 1988;Ulubelen et al, 1989;Todorova et al, 2010). However, no scientific studies are reported on the antioxidant properties of different solvent extracts obtained from different parts of Asphodeline anatolica, which is endemic to Turkey..…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, A.globifera is used as a medicament for alleviating haemorrhoids symptoms, A. lutea and A. taurica are consumed in salads (Tuzlaci, 1985). Owing to their potential use in different purposes, several studies focused on secondary metabolites especially antraquinones, sesquiterpene and naphthalene components of Asphodeline species (Ulubelen et al, 1988;Ulubelen et al, 1989;Todorova et al, 2010). However, no scientific studies are reported on the antioxidant properties of different solvent extracts obtained from different parts of Asphodeline anatolica, which is endemic to Turkey..…”
Section: Introductionmentioning
confidence: 99%
“…Again, several Asphodeline species (A. cilicica, A. damascena, A. globifera, A. lutea and A. taurica) are consumed as salad vegetables in different Turkey regions 22 . Recent studies show that Asphodeline leaves had good nutritional quality with high anthraquinones, essential amino acids and polyphenols levels [23][24][25][26] . However, to the best of our knowledge, the information on the anthraquinone profiles and biological effects of Asphodeline is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…(Asphodelaceae) is a perennial plant native to Mediterranean area, mainly the Middle East-countries [1]. The edible use of its vegetative parts has been known for a long time [2]. The ancient Greeks roasted roots, several Asphodeline species are consumed in salads in Turkey and their leaves are characterized by a good nutritional quality [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chrysophanol was the dominant anthraquinone derivative present in the majority of Asphodeline species [2,4]. Previous investigation of the A. lutea roots led to the isolation of two new anthraquinones for the genus Asphodeline: 1-hydroxy-8-methoxy-3-methylanthraquinone and 1,5,8-trihydroxy-3-methylanthraquinone (7), as well as the known chrysophanol (6), and bianthraquinones:…”
Section: Introductionmentioning
confidence: 99%